"A Chance of Life Against No Chance At All": Intergenerational Minds in Malorie Blackman's Pig-Heart Boy - Silva, Emma-Louise (Cahier voor Literatuurwetenschap, 2024)
Prompted by a newspaper article in the mid-1990s about xenotransplantation, the transplantation of organs from one species into another, children’s literature author Malorie Blackman was inspired to write Pig-Heart Boy (1997), a novel that recounts the experiences of thirteen-year-old Cameron and his pig heart transplant. The novel not only depicts the physical and mental repercussions that the operation has on Cameron, but it also zooms in on how this ethically complex operation affects his grandmother, his parents, and his unborn sibling. Putting the thoughts of these three generations at centre stage, this article positions itself within the field of mind-focused research in literary studies, merging cognitive narratology with children’s literature studies to demonstrate the importance of intergenerational relationships in approaching a challenging future. By doing so, it extends Alan Palmer’s framework of “social minds” (2010) with age-sensitive analyses, providing close readings of how thinking across generations is depicted in Pig-Heart Boy. Through intergenerational exchanges, these characters find out that projecting oneself into the future can be hope-giving and life-affirming, underlining the role that imagination, and by extension, fiction, can play in such complex equations of imagining the future in times of climate crisis and in debates concerning multispecies justice.